Long noncoding RNA EGOT negatively affects the antiviral response and favors HCV replication. (9th June 2016) - Carnero, Elena; Barriocanal, Marina; Prior, Celia; Pablo Unfried, Juan; Segura, Victor; Guruceaga, Elizabeth; Enguita, Mónica; Smerdou, Cristian; Gastaminza, Pablo; Fortes, Puri
Abstract: The role of long noncoding RNAs (lncRNAs) in viral infection is poorly studied. We have identified hepatitisC virus (HCV)‐S timulated lncR NAs (CSRs) by transcriptome analysis. Interestingly, two of these CSRs (PVT1 and UCA1) play relevant roles in tumorigenesis, providing a novel link between HCV infection and development of liver tumors. Expression of some CSRs seems induced directly by HCV, while others are upregulated by the antiviral response against the virus. In fact, activation of pathogen sensors induces the expression of CSR32/EGOT. RIG‐I and the RNA‐activated kinase PKR sense HCV RNA, activate NF‐κB and upregulate EGOT. EGOT is increased in the liver of patients infected with HCV and after infection with influenza or Semliki Forest virus (SFV). Genome‐wide guilt‐by‐association studies predict that EGOT may function as a negative regulator of the antiviral pathway. Accordingly, EGOT depletion increases the expression of several interferon‐stimulated genes and leads to decreased replication of HCV and SFV. Our results suggest that EGOT is a lncRNA induced after infection that increases viral replication by antagonizing the antiviral response. Synopsis: This study shows that the expression of several cellular lncRNAs is induced in HCV‐infected cells, either directly triggered by the viral infection or activated by the antiviral response. One of these is EGOT, which blocks the interferon response and favors viral replication. HCV infection directly induces lncRNAs that partly play relevant roles in cell proliferation, providing a novel link between HCV infection and hepatocarcinogenesis. Also the cellular antiviral response to HCV or other RNA viruses activates the expression of the lncRNAs (such as EGOT). EGOT is induced by NF‐κB after PKR or RIG‐I activation and functions as a negative regulator of the type I IFN response. Increased EGOT expression in infected cells favors viral replication. Abstract : This study shows that the expression of several cellular lncRNAs is induced in HCV‐infected cells, either directly triggered by the viral infection or activated by the antiviral response. One of these is EGOT, which blocks the interferon response and favors viral replication.